TREATMENT OF INVASIVE BLADDER CANCER IN PATIENT AFTER RENAL TRANSPLANTATION - D. V. Perlin; S. P. Darenkov (Вестник трансплантологии и искусственных органов, 2010)
There are case report and literature review of the treatment recurrent bladder cancer after kidney transplantation. Radical cystectomy and Bricker ileal conduit was performed. Detailed operative technique is described. Radical cystectomy is an effective curative treatment for recurrent disease. Bricker ileal conduit is safe and feasible in renal transplant patients.